Effects of an Animal-Derived Biostimulant on the Growth and Physiological Parameters of Potted Snapdragon (Antirrhinum majus L.) - Cristiano, Giuseppe (Front Plant Sci, 2018)
To assess the effect a new animal-derived biostimulant on the growth, root morphology, nitrogen content, leaf gas exchange of greenhouse potted snapdragon, three treatments were compared: (a) three doses of biostimulant (D): 0 (D(0) or control), 0.1 (D(0.1)), and 0.2 g L(−1) (D(0.2)); (b) two biostimulant application methods (M): foliar spray and root drenching; (c) two F(1) Antirrhinum majus L. hybrids (CV): “Yellow floral showers” and “Red sonnet.” The treatments were arranged in a randomized complete-block design with four replicates, with a total of 48 experimental units. Plant height (+11%), number of shoots (+20%), total shoot length (+10%), number of leaves (+33%), total leaf area (+29%), and number of flowers (+59%) and total aboveground dry weight (+13%) were significantly increased by the biostimulant application compared to the control, regardless of the dose. The lowest dose resulted in the best effect on the ground plant dry weight (+38%) and, in order to the root system, on total length (+55%), average diameter (+36%), volume (+66%), tips (+49%), crossings (+88%), forks (+68%), projected (+62%), and total surface area (+28%). Compared to the control, plants treated with the biostimulant significantly enhanced leaf (+16%) and root (+8%) nitrogen content, photosynthetic rate (+52%), transpiration rate (+55%), and stomatal conductance (+81%), although there were no changes in dark-adapted chlorophyll fluorescence. Differences in the application method were not evident in the aboveground morphological traits, except in the plant shoot number (root drenching: +10%). The foliar spray compared to root drenching had a significant effect only on flower dry weight (3.8 vs. 3.0 g plant(−1)). On the other hand, root drenching had a positive effect on ground dry weight (2.7 vs. 2.3 g plant(−1)), root morphology, leaf-N and root-N content (+3%), transpiration rate (+21%), stomatal conductance (+40%), concentration of CO(2) in intracellular spaces (+11%), as well as on the efficiency of Photosystem II (+11%). A higher pot quality was obtained in “Red sonnet” compared to “Yellow floral shower.” Based on our findings, applying the biostimulant to potted snapdragon at the lowest dose, as part of a fertilizing regime, improves the crop quality in an agro-environmental sustainable way.